Spectroscopy and Cyclic Voltammetry Properties of SPEEK/CuO Nanocomposite at Screen-Printed Gold Electrodes - Omolola E. Fayemi; Onkarabile G. Pooe; Funmilola A. Adesanya; Ikechukwu P. Ejidike (Nanomaterials, 2022)
A successful electrochemical study of copper oxide nanoparticles (CuO NPs), sulfonated poly (ether ether ketone) polymer (SPEEK), and sulfonated polyether ether ketone-copper oxide (SPEEK/CuO) nanocomposite on bare gold electrodes was conducted. The synthesized CuO NPs and SPEEK/CuO nanocomposite were characterized using X-ray diffraction (XRD), ultraviolet-visible spectroscopy (UV–Vis), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and electron dispersive spectroscopy (EDS). The XRD showed that the diameter of the CuO NPs synthesized was 20.44 nm. The cyclic voltammetry properties of bare screen-print gold, SPEEK and SPEEK/CuO-modified electrodes were assessed in a 5 mM K3[Fe(CN)6] solution. The electrochemical performance of the fabricated electrodes investigated revealed that CuO NPs improved the electrochemical properties of SPEEK, and the quantum size effect indicated good adsorption by the SPEEK/CuO nanocomposite compared to the SPEEK polymer and the CuO NPs alone. Moreover, the Tafel values indicated the enhanced electrochemical performance of the other electrodes as compared with the SPEEK/CuO nanocomposite. This, therefore, confirmed the successful incorporation of CuO NPs into the SPEEK polymer, as the increased surface area and the interactions between the polymer matrix and CuO fillers improved the electrochemical performance of the electrode.